2011
DOI: 10.1051/0004-6361/201014440
|View full text |Cite
|
Sign up to set email alerts
|

Dust destruction in the ISM: a re-evaluation of dust lifetimes

Abstract: Context. There is a long-standing conundrum in interstellar dust studies relating to the discrepancy between the time-scales for dust formation from evolved stars and the apparently more rapid destruction in supernova-generated shock waves. Aims. We re-examine some of the key issues relating to dust evolution and processing in the interstellar medium. Methods. We use recent and new constraints from observations, experiments, modelling and theory to re-evaluate dust formation in the interstellar medium (ISM). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
224
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(236 citation statements)
references
References 126 publications
(163 reference statements)
10
224
2
Order By: Relevance
“…PAH destruction in the ISM is apparently so effective (Micelotta, Jones & Tielens 2010a) that they do not survive the travel from parent stars to H ii complexes where they are observed. The misbalance between the dust formation and destruction has also been noted for our Galaxy by Jones et al (1994) and Jones, Tielens & Hollenbach (1996) (see however Jones & Nuth 2011). A conventional explanation is that some dust formation in molecular clouds is possible.…”
Section: Introductionsupporting
confidence: 74%
“…PAH destruction in the ISM is apparently so effective (Micelotta, Jones & Tielens 2010a) that they do not survive the travel from parent stars to H ii complexes where they are observed. The misbalance between the dust formation and destruction has also been noted for our Galaxy by Jones et al (1994) and Jones, Tielens & Hollenbach (1996) (see however Jones & Nuth 2011). A conventional explanation is that some dust formation in molecular clouds is possible.…”
Section: Introductionsupporting
confidence: 74%
“…Such a factor 2 variation is expected by considering inhomogeneity or multi-phase structures in the ISM (McKee 1989). Jones & Nuth (2011) pointed out that the estimate of τSN is uncertain; however, as shown later, our choice of βSN nicely explains the dust-to-metal ratio of the Milky Way (Section 4.2). For the destruction of small grains, we conservatively choose α = 1, but later we will also discuss the cases with α < 1.…”
Section: Choice Of Parameter Valuesmentioning
confidence: 62%
“…Besides AGB stars, other sources such as novae, supernovae type II (Wooden et al 1993;Rho et al 2008Rho et al , 2009), young stellar objects (Dwek & Scalo 1980), and red giant stars (Nittler et al 1997) can produce silicate dust. Even dust formation in the ISM may occur in interstellar clouds (Jones & Nuth 2011). Although the amounts of dust contributed by these sources is still debated (Meikle et al 2007;Jones & Nuth 2011), silicate dust is abundant in the ISM and can be found in many different stages of the life cycle of stars (Henning 2010).…”
Section: Introductionmentioning
confidence: 99%